Nanoparticle surface charge influences translocation and leaf distribution in vascular plants with contrasting anatomy - Spielman-Sun, Eleanor; Avellan, Astrid; Bland, Garret D; Tappero, Ryan V; Acerbo, Alvin S; Unrine, Jason M; Giraldo, Juan Pablo; Lowry, Gregory V (Environmental science. Nano, 2019)
Root uptake and translocation of engineered nanoparticles (NPs) by plants are dependent on both plant species and NP physicochemical properties. To evaluate the influence of NP surface charge and differences in root structure and vasculature on cerium distribution and spatial distribution within plants, two monocotyledons (corn and rice) and two dicotyledons (tomato and lettuce) were exposed hydroponically to positively-charged, negatively-charged, and neutral ∼4 nm CeO 2 NPs. Leaves were analyzed using synchrotron-based X-ray fluorescence microscopy to provide lateral Ce spatial distribution. Surface charge mediated CeO 2 NP interactions with roots for all plant species. Positively charged CeO 2 NPs associated to the roots more than the negatively charged NPs due to electrostatic attraction/repulsion to the negatively charged root surfaces, with the highest association for the tomato, likely due to higher root surface area. The positive NPs remained primarily adhered to the roots untransformed, while the neutral and negative NPs were more efficiently translocated from the roots to shoots. This translocation efficiency was highest for the tomato and lettuce compared to corn and rice. Across all plant species, the positive and neutral treatments resulted in the formation of Ce clusters outside of the main vasculature in the mesophyll, while the negative treatment resulted in Ce primarily in the main vasculature of the leaves. Comparing leaf vasculature, Ce was able to move much further outside of the main vasculature in the dicot plants than monocot plants, likely due to the larger airspace volume in dicot leaves compared to monocot leaves. These results provide valuable insight into the influence of plant structure and NP properties on metal transport and distribution of NPs in plants. Root uptake, translocation, and distribution of engineered nanoparticles by plants are dependent on both plant species and nanoparticle surface charge.